Song and Male Quality in Prairie Warblers. (15th June 2016) - Byers, Bruce E.; Akresh, Michael E.; King, David I.
Abstract: To determine if the songs of male prairie warblers could potentially reveal to female listeners information about the quality of singers, we compared various aspects of prairie warbler song structure and performance to attributes that might reflect a male singer's potential to enhance the fitness of his mate. We found that all the tested male attributes—arrival date, age, body size, annual survival, and fledging success—were associated with singing, most with multiple aspects of singing. Several of the song traits that were associated with potential indicators of male quality had also been found previously to be good predictors of female social mate choice. In particular, longer songs with longer elements, performed at lower frequency and with greater consistency, were associated with both female mate choice and potential indicators of quality. Thus, female prairie warblers may assess potential mates with the help of a set of song characteristics that collectively reveal an array of attributes that together indicate overall male quality.